2001
DOI: 10.1029/2000gl012461
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of marine ice beneath the Amery Ice Shelf

Abstract: Abstract.We present a map of the marine ice accreted to the base of the Amery Ice Shelf (AIS), East Antarctica. This map is obtained by converting a Digital Elevation Model (DEM) of the AIS generated from satellite radar altimeter data to an ice thickness map, assuming hydrostatic equilibrium, and subtracting from that a second ice thickness map, derived from airborne radio-echo sounding (RES) measurements. The RES signal does not penetrate the marine ice, so the measurement is only to the meteoric-marine ice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
198
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(213 citation statements)
references
References 19 publications
15
198
0
Order By: Relevance
“…Surface elevation corresponds well to the free-board height derived from locally averaged ice thickness over length scales on the order of 10 ice thicknesses (Figure 2a), and there was no evidence for a thick marine-ice layer from the oceanic borehole at M2. In the 10 MHz radar profiles, we see a bright continuous basal interface typical for a meteoric ice-ocean interface [Fricker et al, 2001]. Furthermore, a significant marine-ice layer (> 8 m, the vertical radar resolution) would be detectable with the low-frequency radar as a deeper fainter continuous interface [Blindow, 1994], which we do not observe.…”
Section: Resultsmentioning
confidence: 72%
“…Surface elevation corresponds well to the free-board height derived from locally averaged ice thickness over length scales on the order of 10 ice thicknesses (Figure 2a), and there was no evidence for a thick marine-ice layer from the oceanic borehole at M2. In the 10 MHz radar profiles, we see a bright continuous basal interface typical for a meteoric ice-ocean interface [Fricker et al, 2001]. Furthermore, a significant marine-ice layer (> 8 m, the vertical radar resolution) would be detectable with the low-frequency radar as a deeper fainter continuous interface [Blindow, 1994], which we do not observe.…”
Section: Resultsmentioning
confidence: 72%
“…1). Greater depths (> 2200 m, Fricker et al 2001) are found near the present ice shelf grounding zone well inland (550 km) from Prydz Bay (Fricker et al 2002). The Amery Depression is linked to the shelf edge by the Prydz Channel, which occupies the western part of the bay and has depths from 700 m below sea level at its inshore end to about 500 m below sea level at the shelf edge (Fig.…”
Section: Regional Settingmentioning
confidence: 99%
“…Ocean circulation and water temperature underneath ice shelves are critical for the ice mass balance; basal accretion amounting to as much as 190 m of ice from the grounding line to the calving front is observed underneath the Amery Ice Shelf in eastern Antarctica (Fricker et al, 2001). On the other hand, warm water has been shown to protrude onto the Amundsen Sea continental shelf in West Antarctica, causing thinning of the floating margin of Pine Island Glacier (Walker et al, 2007;Wåhlin et al, in press).…”
Section: Introductionmentioning
confidence: 99%